2009
DOI: 10.1038/mi.2009.102
|View full text |Cite
|
Sign up to set email alerts
|

Link between allergic asthma and airway mucosal infection suggested by proteinase-secreting household fungi

Abstract: Active fungal proteinases are powerful allergens that induce experimental allergic lung disease strongly resembling atopic asthma, but the precise relationship between proteinases and asthma remains unknown. Here, we analyzed dust collected from the homes of asthmatic children for the presence and sources of active proteinases to further explore the relationship between active proteinases, atopy, and asthma. Active proteinases were present in all houses and many were derived from fungi, especially Aspergillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
142
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(152 citation statements)
references
References 44 publications
9
142
1
Order By: Relevance
“…A. niger conidia administered at relatively low exposure doses consistently induce a highly polarized Th2 response, allergic inflammation, and asthma-like disease in mice (45). This observation appears inconsistent with the prior results of Aimanianda et al, who reported that dormant conidia of a closely related organism, A. fumigatus, elicited little or no inflammation when administered to cultured dendritic cells and mice in vivo (3).…”
Section: Resultscontrasting
confidence: 57%
See 3 more Smart Citations
“…A. niger conidia administered at relatively low exposure doses consistently induce a highly polarized Th2 response, allergic inflammation, and asthma-like disease in mice (45). This observation appears inconsistent with the prior results of Aimanianda et al, who reported that dormant conidia of a closely related organism, A. fumigatus, elicited little or no inflammation when administered to cultured dendritic cells and mice in vivo (3).…”
Section: Resultscontrasting
confidence: 57%
“…All studies were performed 24 h after the final i.n. conidium challenge as previously described (45).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, serological studies in patients with ABPA and SAFS demonstrate IgE responses to fungal products derived from in vivo germination of inhaled conidia into hyphae, as these antibodies exist as a response to fungal exoproducts, hyphal cell wall components expressed during growth phase and cytoplasmic antigens [21,22]. Secondly, there is mounting evidence that fungal hyphal products, including b-glucan and proteases, activate epithelial cells to secrete proinflammatory and Th2-polarising cytokines and chemokines directly via Toll-like receptor-induced signalling, via other innate sensors or via protease-activated receptors [23][24][25][26]. Thirdly, fungal asthma has been linked to host innate immune responses to chitin, a major fungal cell wall component, as chitinase promoter polymorphisms and associated alterations in chitinase activity and elevated chitinase-like protein YKL-40 levels have been found in SAFS in adults and children [27][28][29][30][31][32][33].…”
Section: Antifungal Therapy In Abpa and Safsmentioning
confidence: 99%